2020
DOI: 10.1016/j.radcr.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dissection of the abdominal aorta as a rare complication of Takayasu disease

Abstract: Takayasu's arteritis exposes to complications of varying severity, such as arterial stenosis, thrombosis, and more rarely aneurysms. Aortic dissection is a rare complication of Takayasu's disease, reported in few times in the literature, only 7 of which concern the abdominal aorta. We report the case of a 41-year-old woman followed for Takayasu disease for 15 years, who presented an asymptomatic and chronic dissection of the abdominal subrenal aorta. The patient underwent conservative medical treatment. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The vascular involvements included arterial stenosis, thrombosis, and, rarely, aneurysms. Aortic dissection is very rare, and less than ten cases have been reported involving the abdominal aorta [ 28 ]. Notably, several studies have reported a higher prevalence of IBD among patients with Takayasu arteritis with evidence of genetic overlap [ 29 , 30 ].…”
Section: Large-vessel Vasculitismentioning
confidence: 99%
“…The vascular involvements included arterial stenosis, thrombosis, and, rarely, aneurysms. Aortic dissection is very rare, and less than ten cases have been reported involving the abdominal aorta [ 28 ]. Notably, several studies have reported a higher prevalence of IBD among patients with Takayasu arteritis with evidence of genetic overlap [ 29 , 30 ].…”
Section: Large-vessel Vasculitismentioning
confidence: 99%